Sharing Insights and Strategies from the University of West Georgia. Issue 1 (2nd January 2017) - Heidorn, Brent; Mosier, Brian
Abstract : Teacher candidates need real-world experience in planning, delivering and assessing a comprehensive school physical activity program (CSPAP) so they can be prepared and confident to assist with a CSPAP in whichever school employs them after earning their degree. Physical education teacher education (PETE) programs play a significant role in helping new teachers prepare for school-wide physical activity promotion. This article describes one approach used to assist preservice health and physical education teacher candidates with the development and implementation of specific CSPAP components in a real-world setting. PETE program faculty at the University of West Georgia worked closely with teacher candidates enrolled in the student teaching internship and developed and implemented a series of lectures for teacher candidates related to the successful implementation of a CSPAP in a local school, prior to the student teaching internship. All teacher education candidates in the student teaching internship were asked to assess the needs and opportunities for a CSPAP, develop a proposal for implementation, receive approval from program faculty, implement a CSPAP component, maintain the program, and keep and submit accurate records.